Unemployment protection reforms in Southern European countries between 2004 and 2016 and the trade-off between efficiency and equity - Arcanjo, Maria Manuela (2019)
Efficiency and equity are the two core objectives of unemployment protection schemes. Substantial academic production has focused on theoretically discussing the adverse effects of unemployment benefits as well as their empirical validation. However, the evaluations made of unemployment protection reforms, implemented in every European country, have not as a rule been based on these two state intervention objectives. Hence, this constitutes the main purpose of this article. To this end, we subjected the reform measures undertaken in four southern European countries between 2004 and 2016 to analysis. Three different profiles were identified: the Italian reforms improved both efficiency and equity; Portugal and Spain returned an opposite profile while in Greece, an improvement in efficiency was counterbalanced by a negative impact on equity.